Whole-Cell Photobleaching Reveals Time-Dependent Compartmentalization of Soluble Proteins by the Axon Initial Segment - Nicholson, LaShae; Gervasi, Nicolas; Falières, Thibault; Leroy, Adrien; Miremont, Dorian; Zala, Diana; Hanus, Cyril (Frontiers in Cellular Neuroscience, 2020)
By limiting protein exchange between the soma and the axon, the axon initial segment (AIS) enables the segregation of specific proteins and hence the differentiation of the somatodendritic compartment and the axonal compartment. Electron microscopy and super-resolution fluorescence imaging have provided important insights in the ultrastructure of the AIS. Yet, the full extent of its filtering properties is not fully delineated. In particular, it is unclear whether and how the AIS opposes the free exchange of soluble proteins. Here we describe a robust framework to combine whole-cell photobleaching and retrospective high-resolution imaging in developing neurons. With this assay, we found that cytoplasmic soluble proteins that are not excluded from the axon upon expression over tens of hours exhibit a strong mobility reduction at the AIS – i.e. are indeed compartmentalized - when monitored over tens of minutes. This form of compartmentalization is developmentally regulated, requires intact F-actin and may be correlated with the ultrastructure of the submembranous spectrin cytoskeleton. Our results thus suggest that the rate of protein accumulation in the soma may impact to what extent and over which timescales freely moving molecules can be segregated from the axon. This in turn has important implications for our understanding of compartment-specific signaling in neurons.